Development of Educational Mobile Game for Interactive Learning Media - Sukirman, S; Yuliana, Irma; Sujalwo, S (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2017)
Numerous games are developed today, it leads people to easily obtain many kind of games, for example from online application store such us Google Play and Apple store. This paper reports the development of mobile game application containing educational content for primary school students who study mathematics. The game is called JarMat. The students can learn about addition, subtraction, multiplication, and division by doing tasks that are interactively provided by the game. The tasks are randomly generated by the game system, and players should finish it within a limited time. The game will be over when they fail three times, then the score will be accumulated and stored. Reward will be given if they finish the task before the end of time limit and get a higher score. The difficulty level of the task is determined by the ability of players which depends on experience and time to finish the task. The research of this game development is conducted through reference studies and similar educational games. The game is expected to provide another apps that contains educational content, can be used further for student learning media, mainly 2nd grade of primary school who learn mathematics.